Complicated Paediatric Bronchial Foreign Body: A Novel Extraction Technique (Bangladesh Journal of Otorhinolaryngology, 2021)
A paediatric bronchoscopy procedure for foreign body inhalation is indeed a highly challenging procedure due to multiple risk factors such as lower physiological functional residual capacity and adverse pulmonary function effects by anaesthetic agents in addition to concurrent active lungs infection. Here we elucidate a novel technique of foreign body removal located at the distal airway in a paediatric patient and in a situation where a paediatric flexible bronchoscopy with built-in working channel is not available. A 1-year 7-months-old boy presented with acute respiratory distress syndrome following a one-week history of active respiratory infection. On examination, he was tachypnoeic with audible soft inspiratory stridor and intermittent barking cough despite being supplemented with 3 liters /minute oxygen mask. Chest x-ray showed right upper lobe collapse. He was referred to the otorhinolaryngology team after a suspicious history of foreign body aspiration obtained from his mother. Bedside flexible nasopharyngolaryngoscopy showed granulation tissue at the junction of laryngeal surface of epiglottis and anterior commissure. He underwent emergency direct laryngoscopy, tracheoscopy, bronchoscopy, excision of granulation tissue and removal of foreign body under general anaesthesia. Herein, some of complicated bronchoscopy demand critical thinking of alternative or modified techniques to achieve a successful and safe surgery.Bangladesh J Otorhinolaryngol 2021; 27(2): 177-183